Community participation in COVID-19 prevention and control - Santos, Jonalyn P.; Turingan, Rosalie A.; Mapanao, Nicole P.; Agustin, Angelica B.; Mallo, Colin Joy C.; Palino, Justin Adrian A. (Intelektual Pustaka Media Utama, 2025)
Community-based health protocols are essential strategies for prevention and control of COVID-19 and community participation is an essential contribution of communities during the pandemic. This study assessed community participation to COVID-19 prevention and control activities among barangays in a component city in northern Philippines. This descriptive-quantitative research was conducted in six barangays with the least and most COVID-19 cases in 2021. Barangay residents, officials and health workers were surveyed about community participation using five process indicators namely needs assessment, leadership, organization, resource mobilization and management. A high level of community participation towards COVID-19 prevention and control activities was seen in the barangays with leadership having the highest mean (4.23) and resource mobilization having the lowest mean (3.44). Leadership was significantly the same among all barangays while organization, management, needs assessment and resource mobilization significantly differed according to type of barangay, COVID-19 prevalence and population size. The researchers conclude that there is strong community participation of barangays towards COVID-19 prevention and control activities especially along leadership. However, the capacity of barangays to contribute, mobilize and distribute resources must be improved to maximize community prevention and control of COVID-19.